Relationship of Hemoglobin and Muscle Strength with Quality of Life in Patients with Chronic Renal Failure - Safitri Nur Rahayu; Patwa Amani (Sriwijaya Journal of Medicine, 2024)
The elderly population is vulnerable to degenerative diseases, one of which is Chronic Kidney Disease (CKD). The age of most hemodialysis patients is between 45 and 54 years. Hemoglobin levels and muscle strength in CKD tend to be low which is associated with a decrease in quality of life in CKD. This research is an observational analytical study with a cross-sectional approach. A total of 24 data points from chronic kidney failure patients at Budhi Asih Regional Hospital, Jakarta, were used in this study. Both primary and secondary data were collected. Hemoglobin levels were obtained from medical records, muscle strength was measured using a Camry handgrip dynamometer, and quality of life was assessed through interviews using the Kidney Disease Quality of Life Short Form questionnaire. Statistical analysis was performed using Fisher's exact test with SPSS 29 for Windows, with a p-value of <0.05. Of the 24 study subjects, 20 (83.3%) had anemia, 17 (70.8%) had low muscle strength, and 9 (37.5%) had a poor quality of life. The study's results showed a significant relationship between hemoglobin levels and both muscle strength and the quality of life of chronic kidney failure sufferers, with p-values of 0.012 and 0.022, respectively. There is a relationship between hemoglobin levels and muscle strength and the quality of life of chronic kidney disease sufferers at Budhi Asih Regional Hospital.